2020
DOI: 10.1051/e3sconf/202019501002
|View full text |Cite
|
Sign up to set email alerts
|

TERRE project: interplay between unsaturated soil mechanics and low-carbon geotechnical engineering

Abstract: The geotechnical construction industry is a major component of the overall construction sector and is strategically important in infrastructure development (transportation, flood and landslide protection, building foundations, waste disposal). Although industry and research in the overall construction sector have been investing significantly in recent years to produce innovative low-carbon technologies, little innovation has been created in geotechnical construction industry, which is lagging behind other cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Unsaturated soil mechanics is receiving rising interest from the academic community and the geotechnical construction industry. Some of the appeal derives from the potential use of unsaturated soil mechanics as a tool to reduce the carbon footprint of various civil engineering applications [1][2][3][4][5]. For instance, Speranza et al [6] suggested that the increase in strength resulting from the suction s may be conveniently adopted to reduce the overdesign of the retaining structures in temporary works, leading to a reduction in emissions and materials used.…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated soil mechanics is receiving rising interest from the academic community and the geotechnical construction industry. Some of the appeal derives from the potential use of unsaturated soil mechanics as a tool to reduce the carbon footprint of various civil engineering applications [1][2][3][4][5]. For instance, Speranza et al [6] suggested that the increase in strength resulting from the suction s may be conveniently adopted to reduce the overdesign of the retaining structures in temporary works, leading to a reduction in emissions and materials used.…”
Section: Introductionmentioning
confidence: 99%
“…Slipping surfaces/zones in earth slopes tends to develop below the rooting zone, and failure is often triggered by infiltrating rainwater raising the porewater pressure, thereby reducing the effective stresses and degrading the geomechanical properties. Use of deep-rooted vegetation to remove porewater and increase the matric suction, with effects extending below the rooting zone, is fairly well established [137] and was discussed earlier in the paper. Alternatively, infiltration may be minimised via hydrophobic fungal-hyphal networks [138], or rhizosphere-promoted lateral flow [139].…”
Section: Fungal Mycelial Networkmentioning
confidence: 96%